2022
DOI: 10.1186/s12885-022-10161-x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking-mediated nicotinic acetylcholine receptors (nAChRs) for predicting outcomes for head and neck squamous cell carcinomas

Abstract: Background As a human tumor disease, head and neck squamous cell carcinoma (HNSCC) is associated with a high mortality rate worldwide. Nicotinic acetylcholine receptors (nAChRs) are transmembrane receptor proteins and exert their biological effects following activation by nicotine. We aimed to construct a prognostic signature based on the expression of nAChRs among smokers with HNSCC. Methods The transcriptome profile of nAChRs was obtained from Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…30 Elevated α5 in OSCC may indicate increased EMT phenotypes and decreased cancer-killing immune cells in the TME, both of which are associated with a worse prognosis in many cancers. 26,27,30 On the contrary, though previous study demonstrated that α7-nAChRs in OSCC cell lines are involved in nicotine-mediated cell survival and cisplatin resistance, 45 the α7 expression level was found to have insignificant survival influence in HNC patients, 46 which is consonant with our study.…”
Section: Discussionsupporting
confidence: 89%
“…30 Elevated α5 in OSCC may indicate increased EMT phenotypes and decreased cancer-killing immune cells in the TME, both of which are associated with a worse prognosis in many cancers. 26,27,30 On the contrary, though previous study demonstrated that α7-nAChRs in OSCC cell lines are involved in nicotine-mediated cell survival and cisplatin resistance, 45 the α7 expression level was found to have insignificant survival influence in HNC patients, 46 which is consonant with our study.…”
Section: Discussionsupporting
confidence: 89%
“…As an emerging technological tool, data mining has been widely applied in the field of medicine. It can assist researchers in extracting valuable information from massive data, such as identifying the pathogenesis of cancer ( 6 ), recognizing patients’ risk factors ( 7 ), and predicting prognosis ( 8 ). Additionally, data mining can help discover novel treatment strategies and drugs, as well as optimize existing treatment regimens.…”
mentioning
confidence: 99%